RESEARCH AND DEVELOPMENT IN WOUND MANAGEMENT PRODUCTS: A BRIEF REVIEW - Geetha V, Surya; Gupta N, Vishal; Dv, Gowda; Pk, Kulkarni (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Wound can be defined as any process which leads to the disruption of the normal architecture of a tissue. They may be closed or open, for example, abrasions, lacerations, avulsions, ballistic and excised, or surgical wounds. Successful wound care includes advancing patient local and systemic conditions in conjunction with a perfect injury healing condition. Numerous wide assortments of dressing materials are accessible both for extreme and persistent non-healing wounds. A wide range of wound healing products have been produced to impact this injury condition to give a non-pathogen, ensured, and clammy region for healing to happen. A perfect injury dressing ought to limit loss of protein, electrolytes, and liquids from twisted and to diminish pain and contamination alongside wound healing. More current products are as of now being utilized to supplant or enlarge different substrates in the injury healing period. There is a sharp complexity to prior routine of wound administration, where the injury is permitted to dry, yet the present advancement was to move forward to the idea of wet injury recovering. This review of the present wounding periphery in wound recovery occurs at the most recent utilizations of silver and the employments of negative pressure wound gadgets, propelled dressings and skin substitutes, and biologic injury items including development of hydrogels and hyperbaric oxygen as an aid in wound mending. With the advancement of accessible dressings, the objective is to locate the most proper methodology or blend of modalities to optimize wound healing.